2022
DOI: 10.1021/jacs.2c00322
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Multiple Quantum-Interfered States via Through-Space and Through-Bond Synergistic Effect in Foldamer-Based Single-Molecule Junctions

Abstract: The construction of multivalued logic circuits by multiple quantum-interfered states at the molecular level can make full use of molecular diversity and versatility, broadening the application of molecular electronics. Understanding charge transport through different conducting pathways and how they interact with each other in molecules with a secondary structure is an indispensable foundation to achieve this goal. Herein, we elucidate the synergistic effect from through-space and through-bond conducting pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…By varying this connectivity, intramolecular quantum interference (QI) effects can be switched between constructive QI (CQI) and destructive QI (DQI). Single-molecule junctions provide an effective platform for studying QI effects in single molecules and dimers. , In the past two decades, single-molecule experimental measurements and theories , have revealed a wealth of fundamental knowledge about dimers composed of aromatic or poly-aromatic molecules, including the effects of the electron-transport distance, stacking mode, and stretching process on charge transport. Especially, how to use QI to control the charge and energy flow through such structures and further construct the circuits has attracted extensive attention. , Recently, it was demonstrated that these quantum effects can be translated into self-assembled molecular layers (SAMs), thereby opening routes to the design of 2D organic materials, whose room-temperature transport properties are controlled by quantum interference. A key feature of SAMs, which is not manifested in single-molecule junctions, is the presence of intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…By varying this connectivity, intramolecular quantum interference (QI) effects can be switched between constructive QI (CQI) and destructive QI (DQI). Single-molecule junctions provide an effective platform for studying QI effects in single molecules and dimers. , In the past two decades, single-molecule experimental measurements and theories , have revealed a wealth of fundamental knowledge about dimers composed of aromatic or poly-aromatic molecules, including the effects of the electron-transport distance, stacking mode, and stretching process on charge transport. Especially, how to use QI to control the charge and energy flow through such structures and further construct the circuits has attracted extensive attention. , Recently, it was demonstrated that these quantum effects can be translated into self-assembled molecular layers (SAMs), thereby opening routes to the design of 2D organic materials, whose room-temperature transport properties are controlled by quantum interference. A key feature of SAMs, which is not manifested in single-molecule junctions, is the presence of intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The reason might be that the transmission in m -OCB and p -OCB is split into terms that are dominated by through-space transport and through-bond transport. 24 It is speculated that the higher conductance of m -OCB is mainly contributed by the stronger through-space transport between two phenyl groups than that in p -OCB . The short junction length of m -OCB also contributes to its high conductance.…”
Section: Resultsmentioning
confidence: 99%
“…22 Molecular wires based on noncovalent through-space conjugation have been widely studied in recent decades, in which the π-electrons of adjacent stacked aromatic rings realize charge transport through spatial interaction, bringing unique physical and chemical phenomena. [23][24][25] Based on the above discussion, it is worthwhile to further explore the properties of molecules with the same molecular skeleton but different substitution positions of the anchor group, particularly for the o-carborane-based molecules with multiple conduction channels, which will reveal the relationship between QI effects, molecular configurations, and charge transport paths. Herein, we choose the o-carborane skeleton as the building block for molecular wires and explore the influence of through-space transport on conductance by changing the anchor group configuration ( p-OCB, m-OCB and o-OCB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conductance ( G ) of a single molecule junction within a small bias window is proportional to the transmission coefficient T ( E F ), which is given by the Landauer formula:where e is the electron charge and h is Plank's constant. Furthermore, the transmission coefficient can be decided by the square of the zeroth Green's function as follows: 13 Herein, γ is the coupling to the electrodes, G r ( E ) is the retarded Green's function, C rk and are the k th MO coefficients at atom sites r and s , and ε k is the k th MO energy.…”
Section: Resultsmentioning
confidence: 99%